Answer:
x = 4, x ≠ -1
Step-by-step explanation:
√3x + 4 = x
(√3x + 4)² = x² (Square both sides to get rid of the radical.)
3x + 4 = x²
0 = x² - 3x - 4 (Set everything to 0 by moving everything to one side.)
0 = (x - 4)(x + 1) (Factor.)
x = 4 x = -1
Now we need to check for extraneous solutions:
√3(4) + 4 = 4
√12 + 4 = 4
√16 = 4
4 = 4
√3(-1) + 4 = -1
√-3 +4 = -1
√1 = -1
1 ≠ -1
-1 is an extraneous solution.
Answer:
I believe your answer is -7/54
That would be a 45 degree angle
To factor,
<h2>
[[[</h2>
1) First multiply coefficient of a² and constant no,
That is,
3×(-42)=-126
Since the<u> resultant no is negative</u>, you should find two such factors of 126 <u>which</u> <u>will give us the coefficient of a (=11)</u> on subracting those factors.
2) Find the factor
126=2×3×3×7
=18×7
18 and 17 are factors of 126
Also,18-7 =11.
So they are required factors for factoring,
<h2>
]]]</h2>
Once you have understood above steps you can solve on your own. All you need to do is split 11 into factors ,take common terms and you will get answer.
<u>Answer:</u>
3a²+11a-42
=3a²+(18-7)a -42
=3a²+18a-7a-42
=3a(a+6) -7(a+6)
=(a+6)(3a-7)